Cerebral Air Embolism: A Non-Thrombotic Cause of Acute Stroke - Squitieri, Martina; Poggesi, Anna; Cecchi, Andrea; Lascio, Gabriella Di; Gadda, Davide; Lombardo, Ivano; Pescini, Francesca (Archives of Clinical and Medical Case Reports, 2020)
Background: Embolic strokes are due to occlusion of brain arteries mainly by clots, less frequently by non-thrombotic material. Cerebral air embolism (CAE) may occur as complication of medical procedures, although non-iatrogenic sources have been reported. It is a life-threating emergency with poor prognosis both in terms of mortality and disability. Hyperbaric oxygen therapy (HOT) is the gold standard treatment. Methods: We report a series of 4 in-hospital patients with CAE for whom stroke neurologists were activated for acute management. Three patients developed neurological disturbances soon after central venous catheter manipulation, one patient, affected by chronic obstructive pulmonary disease, after prolonged coughing with respiratory distress. Results: All patients experienced seizures, loss of consciousness and bilateral neurological signs. Acute brain computed tomography (CT) revealed intracranial air bubbles. One patient underwent HOT 3 hours after symptoms onset and fully recovered, for the others HOT was contraindicated: one died and 2 presented severe neurological sequelae. Conclusions: Physicians involved in acute stroke management should be aware of CAE and promptly recognize it, especially for in-hospital strokes, and manage this condition together with anesthetists and hyperbaric physicians. <gdiv></gdiv>